TGR5 Regulates Macrophage Inflammation in Nonalcoholic Steatohepatitis by Modulating NLRP3 Inflammasome Activation - Shi, Yong; Su, Wantong; Zhang, Lei; Shi, Chengyu; Zhou, Jinren; Wang, Peng; Wang, Hao; Shi, Xiaoli; Wei, Song; Wang, Qi; Auwerx, Johan; Schoonjans, Kristina; et al. (Frontiers in Immunology, 2021)
Nonalcoholic steatohepatitis (NASH) is a chronic liver disease associated with dysregulation of liver metabolism and inflammation. G protein-coupled bile acid receptor 1 (TGR5) is a cell surface receptor that is involved in multiple metabolic pathways. However, the functions of TGR5 in regulating macrophage innate immune activation in NASH remain unclear. Here, we found that TGR5 expression decreased in liver tissues of humans and mice with NASH. Compared with wild-type (WT) mice, TGR5-knockout (TGR5−/−) mice showed an aggravation of liver damage, increased levels of pro-inflammatory factors, and enhanced M1 polarization of macrophage. Moreover, TGR5 deficiency facilitated macrophage M1 polarization by promoting NLRP3 inflammasome activation and caspase-1 cleavage. Altogether, our findings revealed that TGR5 signaling attenuated the liver steatosis and inflammation, and inhibited NLRP3-mediated macrophage M1 polarization in NASH.